Combined probiotics attenuate chronic unpredictable mild stress-induced depressive-like and anxiety-like behaviors in rats - Huang, Li; Lv, Xia; Ze, Xiaolei; Ma, Zewei; Zhang, Xuguang; He, Ruikun; Fan, Junting; Zhang, Meilin; Sun, Boran; Wang, Fang; Liu, Huan (Frontiers in Psychiatry, 2022)
There is increasing evidence that probiotics can effectively improve depression-like and anxiety-like behavior. However, the underlying mechanisms are still unclear and the effects of single versus combined probiotics on depression and anxiety is unknown. This study aimed to determine whether combined probiotics could attenuate chronic unpredictable mild stress (CUMS) induced depressive-like and anxiety-like behavior and its potential mechanisms. Rats underwent CUMS treatment and then administered Lactobacillus rhamnosus HN001 (HN001) or Bifidobacterium animalis subsp. lactis HN019 (HN019), alone or in combination. Levels of neurotransmitters, inflammatory factors, and the gut microbiota were measured. HN001 and(or) HN019 treatment improved depressive-like and anxiety-like behavior of rats, including increased moving distance and exploratory behavior (p<0.05). In addition, HN001 and/or HN019 intervention amended gut microbiota structure changes induced by CUMS (p<0.05), and remarkably normalized levels of 5-HT, DA, NE, HVA, DOPAC, HIAA, TNF-ɑ, IL-6, IL-18 and IL-1β in CUMS rats (p<0.05). Furthermore, the effects of combined probiotics on decreasing inflammation and improved gut microbiota (Chao1 index and ACE index, p<0.05) were superior to the single probiotics. Moreover, spearman analysis showed that there is a certain correlation between the differential microbiota, such as Firmicutes, Bacteroidetes, Verrucomicrobias, Proteobacterias and Actinobacterias, inflammation and neurotransmitters. These findings suggested that combined probiotics can alleviate rodent depressive and anxiety-like behaviors induced by CUMS, which was possibly associated with the alterations in the gut microbiota composition and increased neurotransmitters and decreased inflammatory factors.